METHODOLOGY FOR QUANTIFYING GREENHOUSE GAS EMISSIONS IN THE DEVELOPMENT OF GREEN TOURISM - Rasulova Nigora Yusupovna (Modern American Journals, 2025)
This article examines the methodology for quantifying greenhouse gas emissions in the development of green tourism, with an emphasis on sustainable practices that balance environmental protection, cultural preservation, and economic growth. The study analyzes Uzbekistan's rich natural landscapes, historical heritage, and biodiversity to identify key opportunities for green tourism, including ecotourism, agrotourism, and community tourism.
Keywords: Green tourism, green development, green tourism models, CO2, greenhouse gases, sustainable development.